Experimental Study of Flexural Behavior of Reinforced Concrete Beam Strengthened with Prestressed Textile-Reinforced Mortar - Jongho Park (Materials, 2020)
In this study, nine specimens were experimentally tested to analyze the strengthening efficiency of textile-reinforced mortar (TRM) and the difference in flexural behavior between prestressed and non-prestressed TRM-strengthened reinforced concrete beam. The test results show that TRM strengthening improves the flexural strength of TRM-strengthened reinforced concrete beams with alkali-resistant-(AR-) glass textile as well as that with carbon textile. However, in the case of textile prestressing, the strengthening efficiency for flexural strength of the AR-glass textile was higher than that of the carbon textile. The flexural stiffness of AR-glass textiles increased when prestressing was introduced and the use of carbon textiles can be advantageous to reduce the decreasing ratio of flexural stiffness as the load increased. In the failure mode, textile prestressing prevents the damage of textiles effectively owing to the crack and induces the debonding of the TRM.